Full and productive employment in developing economies towards the sustainable development goals - Islam, Rizwanul (Routledge, 2020)
"This book presents a broad framework which could enable us to pursue the challenging goal of full, productive employment in developing countries. It revisits the conceptual foundations of full employment, and carefully examines the issue of suitable indicators for monitoring progress"--
Description based on online resource; title from digital title page (viewed on September 04, 2019)
Keywords: Full employment policies / Developing countries; Labor market / Developing countries; Sustainable development / Developing countries